2005
DOI: 10.1159/000087784
|View full text |Cite
|
Sign up to set email alerts
|

In-Patient Treatment of Mothers with Depressive Disorders – Does Joint Admission of Their Children Have a Negative Effect on the Results of Treatment?

Abstract: Background: There is disagreement whether in-patient psychotherapeutic treatment results for women whose children are cohospitalised with them would be better if the mothers were hospitalised without children. The purpose of this study was to examine this question in the case of mothers with depressive symptoms. Methods: The treatment results for 43 female in-patients (21 with and 22 without accompanying children) in a prospective, randomised, controlled study were compared. The period of observation was 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It has been reported that highly motivated patients with generalized anxiety disorder were able to benefit significantly more from psychosomatic therapy during their hospital stay compared to less motivated patients (15). A study on depression also reported that patients with relatively high levels of depressive symptoms who were motivated early in their treatment could benefit significantly more from psychosomatic therapy than patients with low levels of motivation (16). Furthermore, psychotherapy, which focuses on motivation, is also widely known (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that highly motivated patients with generalized anxiety disorder were able to benefit significantly more from psychosomatic therapy during their hospital stay compared to less motivated patients (15). A study on depression also reported that patients with relatively high levels of depressive symptoms who were motivated early in their treatment could benefit significantly more from psychosomatic therapy than patients with low levels of motivation (16). Furthermore, psychotherapy, which focuses on motivation, is also widely known (17).…”
Section: Discussionmentioning
confidence: 99%
“…Involving families of troubled girls in all phases of treatment is believed to be essential and aids both in successful reintegration of the patient into the community and prevention of relapse [13,[15][16][17][27][28][29][30][31][32][33][34] . This study shows that even bullying girls were able to cope well with BSFT.…”
Section: Discussionmentioning
confidence: 99%
“…Involving families of troubled girls in all phases of treatment is believed to be essential and aids both in successful reintegration of the patient into the community and prevention of relapse [13,[15][16][17][27][28][29][30][31][32][33][34] . This study shows that even bullying girls were able to cope well with BSFT.…”
Section: Discussionmentioning
confidence: 99%